The occurrence of Brassica montana Pourr. (Brassicaceae) in the Italian regions of Emilia-Romagna and Marche, and in the Republic of San Marino - Maggioni, L.; Alessandrini, A. (Pensoft Publishers, 2019)
Brassica montana Pourr., a wild relative of the Brassica oleracea L. cole crops (broccoli, cabbage, cauliflower, etc.), deserves special attention for its potential to easily transfer agronomically useful traits to related crops. Monitoring existing B. montana populations is the first step to enabling long-term conservation and management of wild genetic resources. In this paper, we focus on all the B. montana reports for the Italian regions of Emilia-Romagna and Marche, and additionally for the neighbouring Republic of San Marino. According to our analysis, the presence of B. montana is confirmed in the Marche and the Republic of San Marino, but not in Emilia-Romagna.